Pengaruh Work-Life Balance terhadap Employee Performance Melalui Employee Loyalty pada Perusahaan Manufaktur PT Boma Bisma Indra - Sheriff Moslem Alfarizi; Khoirur Rozaq (Universitas Negeri Surabaya, 2025)
This study explores the influence of work-life balance on employee performance through employee loyalty at PT XXX. A good balance between work and personal life is considered an important factor in creating a healthy and productive work environment, which can strengthen employee loyalty and improve performance. This research uses a quantitative approach by distributing questionnaires to 40 permanent employees of the company. The data were analyzed using the Partial Least Squares (PLS) method with the help of SmartPLS software. The results show that work-life balance has a positive and significant impact on employee loyalty, and in turn, employee loyalty positively affects employee performance. Furthermore, employee loyalty is found to significantly mediate the relationship between work-life balance and employee performance. These findings highlight the importance of maintaining work-life balance not only to increase employee loyalty but also to improve performance outcomes. It is suggested that companies implement policies and build work environments that support work-life balance as part of their human resource strategy. This study contributes to the literature on human resource management, especially in the manufacturing context, and provides practical insights for managers in developing effective strategies to enhance both employee well-being and organizational performance in competitive business environments.